FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN SEKTOR INDUSTRI - Jonathan Jonathan; Jamaludin Iskak (Jurnal Paradigma Akuntansi, 2026)
The purpose of this research is to examine the effect of Return On Equity, Earning Per Share, and Return On Asset on stock price of industry sector companies listed on the Indonesia Stock Exchange during 2019-2021. Sample was selected using purposive sampling method and results with 36 companies. Data processing techniques using multiple regression analysis with the Eviews 10 program and Microsoft Excel 2016. The results of this study indicate that Return On Equity, Earning Per Share and Return On Asset have insignificant effect on profitability, and firm size has a positive and significant effect on profitability. The implication is the need to To increase stock prices, companies need to pay attention and maintain the company's financial ratios in order to attract investors and increase stock prices.